Masked mastoiditis with meningitis : do we treat ct scan? - Amiruddin, Salman Bin; Rahman, Roslenda Abdul (Bangladesh Journal of Medical Science, 2017)
Otogenic infection is the most common cause of meningitis.Therefore, it should be ruled out during clinical assessment of a patient with any intracranial infection. Masked mastoiditis is a known intratemporal complication of acute otitis media after inadequate antimicrobial treatment. It is defined as inflammation of mucosal lining and bony structures of the mastoid air cells with an intact tympanic membrane. It should be regarded as the source of infection in a patient with meningitis and positive radiological findings of mastoiditis even though the patient does not have any evidence of ear infection clinically. We report a case of bacterial meningitis following masked mastoiditis in an 68-years-old man. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.458-460